Effectiveness of extended pelvic lymphadenectomy in the survival of prostate cancer: a systematic review and meta-analysis - García-Perdomo, Herney Andrés (Cent European J Urol, 2018)
INTRODUCTION: To determine the effectiveness and safety of extended pelvic lymphadenectomy compared with standard lymphadenectomy in the overall, cancer-specific survival and biochemical recurrence-free survival of patients with localized prostate cancer who underwent radical prostatectomy. MATERIAL AND METHODS: Clinical trials and cohort studies were included without language restrictions with the following participants: men older than 40 years of age diagnosed with localized prostate cancer who received radical prostatectomy plus pelvic lymphadenectomy. Standard vs. extended pelvic lymphadenectomy were compared. The primary outcomes were overall and cancer-specific survival. A search strategy in MEDLINE, EMBASE, CENTRAL, LILACS, and other databases was conducted to obtain published and unpublished literature. The risk of bias was evaluated with the Cochrane Collaboration tool. The statistical analysis was performed in STATA 14. RESULTS: Six studies were included, of which only one was experimental; the other studies were cohort studies. The surgical technique was robot-assisted in three studies. Two studies only had information concerning the adverse effects. It was not possible to include one clinical trial that met the criteria because an erratum was published in which falsification of the experimental data was proven. There was a biochemical recurrence-free survival hazard ratio (HR) = 0.62 and a 95% confidence interval (CI) (0.36 to 0.87). CONCLUSIONS: According to current literature, a mild difference was evident favoring the extended lymphadenectomy in biochemical recurrence-free survival. Additionally, there was no evidence to draw a conclusion regarding the overall survival since we did not find any studies concerning this outcome.